Pre- and postoperative carcinoembryonic antigen determinations in hepatic resection for colorectal metastases predictive value and implications for adjuvant treatment based on multivariate analysis - Hohenberger, Peter; Schlag, Peter M.; Gerneth, Thomas; Herfarth, Christian (Annals of surgery, 1994)
Objective - The object of this study was to evaluate the prognostic significance of pre- and postoperative serum carcinoembryonic antigen (CEA) levels in the resectional treatment of colorectal hepatic metastases. The main question was whether postoperative CEA levels correlated with survival and the time to recurrence. - Summary Background Data - Despite numerous investigations on prognostic factors in colorectal cancer, only sparse data are available to estimate the patient's individual risk for tumor recurrence postoperatively. It is controversial whether preoperative CEA values are of prognostic significance, and after observing the kinetics of CEA decline, elevated CEA levels postoperatively were found to be an ominous sign. CEA therefore could indicate the presence of a tumor burden after resection. - Methods - One hundred sixty-six patients undergoing hepatic resection for colorectal metastases with curative intent were prospectively documented and underwent multivariate analysis for indicators of prognosis. - Results - Abnormal preoperative CEA levels were not of prognostic significance compared with values within the normal range (survival, 36 vs. 30 months; p = 0.12; disease-free survival, 12 vs. 10 months; p = 0.82). The postoperative serum CEA level, however, was the most predictive factor with regard to survival and the disease-free interval. Patients in whom CEA levels were abnormal before surgery and returned into the normal range after resection had significantly better survival times (37 vs. 23 months, p = 0.0001) and disease-free survival times (12 vs. 6.2 months, p = 0.0001) compared with patients with persistently abnormal values.
Gesehen am 29.09.2025